Acquisition of high-level mupirocin resistance in CoNS following nasal decolonization with mupirocin. (23rd December 2014) - Hetem, David J.; Vogely, H. Charles; Severs, Tim T.; Troelstra, Annet; Kusters, Johannes G.; Bonten, Marc J. M.
Abstract: Objectives: The association between mupirocin use and plasmid-based high-level resistance development mediated through mupA in CoNS has not been quantified. We determined acquisition of mupirocin resistance in Staphylococcus aureus and CoNS in surgery patients treated peri-operatively with mupirocin. Patients and methods: Patients admitted for surgery were treated with nasal mupirocin ointment and chlorhexidine soap for 5 days, irrespective of S. aureus carrier status. Nasal swabs were obtained before decolonization (T1) and 4 days after surgery (T2) and were inoculated onto agars containing 8 mg/L mupirocin. Staphylococci were identified by MALDI-TOF MS and mupirocin resistance was confirmed by Etest. Results: Among 1578 surgical patients, 936 (59%) had nasal swabs obtained at T1 and T2; 192 (21%) patients carried mupirocin-resistant CoNS at T1 and 406 (43%) at T2 ( P < 0.001). Of 744 patients not colonized at T1, 277 acquired resistance (37%), corresponding to an acquisition rate of 7.4/100 patient days at risk. In all, 588 (97%) of 607 mupirocin-resistant CoNS had an MIC >256 mg/L (high level) and 381 of 383 (99.5%) were mupA positive. No acquisition of mupirocin resistance was observed in S. aureus . Conclusions: Acquisition of mupirocin resistance following decolonization was widespread in CoNS and absent in S. aureus . As almost all isolates harboured the mupA gene, monitoring resistance development in S. aureus when decolonization strategies containing mupirocin are used is recommended.